Peningkatan Hasil Belajar Siswa pada Materi Tata Surya Melalui Media Audio Visual - Abdillah, Fitria Pitaloka (LPPM Universitas Terbuka, 2024)
Post-pandemic learning requires adaptation to enhance students' readiness to learn. Observations indicate that students' self-directed learning motivation is low, in line with learning outcomes below the Minimum Competency Criteria (KKM). A lack of enthusiasm in the learning process was also noted. To address these issues, Classroom Action Research (CAR) was conducted to improve students' mastery of science concepts on the Solar System topic using audio-visual media. The research was carried out at SDN Lubang Buaya Bekasi with 40 sixth-grade students in the even semester of the 2022/2023 academic year. The study was conducted in 2 cycles, each consisting of two meetings. Each cycle involved planning, action implementation, evaluation, and reflection stages. The results showed an increase in student activity and concept mastery, with the class average rising from 72.00 in cycle I to 86.00 in cycle II. Classical completeness was achieved with 90% of students meeting the KKM in cycle II. The research methods included observation, interviews, and written tests. Data collection techniques included observation sheets, field notes, and evaluation questions. These results demonstrate that the use of audio-visual media positively impacts the mastery of Solar System concepts.